Dinamika Pengaruh Organisasi Masyarakat dalam Pengisian Anggota Komisi Pemilihan Umum di Daerah - Busthomi, Masum; Satriawan, M. Iwan (Journal of Political Issues, 2020)
General election is a mechanism that functions as a means of implementing principles of democracy. The election goes well, KPU is formed as independent and enduring institution that has authority to hold election such as presidential, legislation and regional head election. To hold elections, a KPU comissioner from the community was chosen through the formation selection team (Timsel) of an independent. The selection team (Timsel) also isn’t separable from elements of societis such as academics, community leaders and election experts. This research use of qualitative methode to expressing problems. Focus writer directed to social reality towards an object for study, so this research looked at individuas and social organization as part of a strength that can determine whether the candidate of KPU is selected or not. The result of the analysis shows that in the practice of election commisioners KPU are not only determined by personal abilities but also influenced by the ideology of community organizations in the selection team.Hence the composition of the number of selection teams from one community organization will affect the number of election candidate of the KPU commisioners who have the same ideology with one of these organization.